Diversity in jackfruit (Artocarpus heterophyllus Lam.): insights into fruit characterization for the identification of superior genotypes. Issue 5 (22nd October 2020) - Dhakar, M.K.; Das, Bikash; Sarkar, P.K.; Nath, Vishal; Singh, A.K.; Bhatt, B.P.
Abstract: Jackfruit ( Artocarpus heterophyllus Lam.) is a nutritious crop from the Moraceae family. The current study was undertaken to evaluate the phenotypic diversity of fruit characteristics using a set of 27 standardized fruit descriptors to describe 28 jackfruit genotypes. These data were used to identify the superior jackfruit genotype that could be used for commercial cultivation. The data revealed a wide range of differences among the genotypes for all the traits studied. Cluster analysis classified the genotypes into four major groups that confirmed the wide diversity among them. Principal component analysis (PCA) also revealed that 80.22% of the variability among the jackfruit genotypes was explained by the first five principal components (PCs). Based on the overall results, the Indian Council of Agricultural Research, Research Complex for Eastern Region (ICAR-RCER) JS 6/3 and 10/3 genotypes were found to be the most promising for table purposes (medium fruit size, pulp percentage >50 and total soluble solid (TSS) >20°Brix), whereas the ICAR-RCER JS 7/7 genotype with large fruit size, pulp percentage >50 and TSS >20°Brix was found to be suitable for processing. The coefficient of variation was the least for traits such as TSS (12.56%) and average seed length (13.56%). Hence, priority may also be given to the TSS and seed size when exploring promising genotypes and operating a selection procedure for crop improvement in jackfruit. The information generated under the study forms a potential baseline for fruit breeders to use in selecting genotypes with superior fruit qualities for jackfruit crop improvement programmes in the future.